Pengaruh Teknik Relaksasi Nafas Dalam Dengan Aroma Terapi Lavender Terhadap Tingkat Nyeri Post Operasi Phacoemulfikasi Menggunakan Anestesi Lokal Kamar Operasi RSUD Cilincing Tahun 2023 - Putri Lenggo Geni; Bambang Suryadi; Susaldi Susaldi (STIKes Ibnu Sina Ajibarang, 2024)
Patients experience pain after surgery, which might lead to problems. Negligible delay in treatment will result in serious complications including elevated vital signs (blood pressure, pulse, respiration, temperature, and bleeding) and a slowed healing rate. A non-pharmacological approach that has been shown to alleviate pain, enhance blood oxygenation, and expand the patient's airways is the deep breathing relaxation method. The purpose of this research is to find out how much pain patients experience following phacoemulsification surgeries performed with local anesthesia in the operating rooms at Cilincing Hospital in 2023 respond to breathing relaxation methods and lavender aroma therapy. This study employed a quasi-experimental approach using a one-group pretest-posttest to collect quantitative data. This research included 114 patients who had postoperative phacoenulsification under local anesthesia in the operating room of Cilincing Hospital. In this study, the incidental sampling method was used for the sampling process. This research included 35 patients as a sample. This study tool was acquired by use of the Numeric Rating Scale (NRS) for pain. We utilize the Paired T-test to analyze the data. In 2023, the operating room of Cilincing Hospital used local anesthesia for phacoemulsification surgery, and the results of the statistical test indicated that the p value of 0.000, which means P<0.05. Therefore, it can be inferred that the level of pain after the procedure was affected by the deep breathing relaxation technique combined with lavender aroma therapy. Reducing discomfort after phacoemulsification surgery with local anesthetic may be achieved with the use of lavender aroma therapy and deep breathing exercises performed by healthcare professionals.